FACTORS AFFECTING CORPORATE FINANCIAL PERFORMANCE IN THE BASIC MATERIALS INDUSTRY IN INDONESIA - Berlianty, Berlianty; Salim, Susanto (Graduate Program of Universitas Tarumanagara, 2024)
This study aims to obtain empirical evidence about the effect of environmental performance, environmental cost, and company size on the financial performance of basic materials companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sample number in this study was 19 basic materials companies selected by purposive sampling method. The research data were analyzed using multiple linear regression analysis techniques processed with SPSS software. The results of this study indicate that environmental costs have a significant negative effect on financial performance. Environmental performance and company size do not have a significant effect on financial performance. This research implies that investors pay less attention to the company's environmental performance. Thus, the company should pay more attention to the environmental costs incurred so as not to have an impact on decreasing financial performance.